Integrated analysis from multi-center studies identities m7G-derived modification pattern and risk stratification system in skin cutaneous melanoma - Zhang, Xin; Miao, Ying; Sun, Hao-Wen; Wang, Yi-Xiao; Zhao, Wen-Min; Pang, A-Ying; Wu, Xiao-Yan; Shen, Cong-Cong; Chen, Xiao-Dong (Frontiers in Immunology, 2022)
In recent years, m7G modification patterns have been proven to play an important role in RNA post-transcriptional modification and protein translation. However, the potential role of m7G modification patterns in assessing the prognosis of Skin cutaneous melanoma (SKCM) and the tumor microenvironment (TME) has not been well studied. In this paper, we investigated and finally identified 21 available m7G-related genes. We discovered that m7G cluster B was associated with high immune activation levels and good survival prognosis by using hierarchical clustering (K-means) to classify 743 SKCM patients into three m7G-modified subtypes named m7G cluster-A, B, C and analyzing the survival prognosis, the characteristics of biological behavior, and cell infiltration in TME of different subpopulations. We further identified the differentially expressed genes (DEGs) in the three subgroups using the "limma" package. Based on the DEGs, K-means was used to divide the patients into different gene subgroups named gene cluster-A, B, C. Consistent with the m7G cluster B, gene cluster B also showed better survival prognosis and immune infiltration levels. Then, SKCM patients were divided into high and low m7G score subgroups using principal component analysis (PCA) according to their prognosis-related DEGs, with higher subgroups having better prognostic outcomes and being strongly correlated with increased immune infiltration. Univariate and multivariate Cox regression analysis showed that risk score was a strong independent prognostic indicator. By combining risk scores with tumor clinicopathological features, a nomogram was constructed to predict the prognosis of SKCM patients. In conclusion, m7G modification pattern plays an important role in TME. An individualized m7G score can better evaluate the m7G modification pattern, immune infiltration level of patients and correlate with patient prognosis and immune response, which provides a new idea for SKCM treatment.